Invite Only Dinner with Bernard Witkin at Basque Hotel - Watkins, Howard::::::::: (1986)
Max Hayden sharing a story; facing: David St. Louis, Robert Sears, Judge Milo Popovich, Justice George Brown and Max Hayden